PRMT7 Interacts with ASS1 and Citrullinemia Mutations Disrupt the Interaction. Issue 15 (21st July 2017) - Verma, Mamta; Charles, Ramya Chandar M.; Chakrapani, Baskar; Coumar, Mohane Selvaraj; Govindaraju, Gayathri; Rajavelu, Arumugam; Chavali, Sreenivas; Dhayalan, Arunkumar
Abstract: Protein arginine methyltransferase 7 (PRMT7) catalyzes the introduction of monomethylation marks at the arginine residues of substrate proteins. PRMT7 plays important roles in the regulation of gene expression, splicing, DNA damage, paternal imprinting, cancer and metastasis. However, little is known about the interaction partners of PRMT7. To address this, we performed yeast two-hybrid screening of PRMT7 and identified argininosuccinate synthetase (ASS1) as a potential interaction partner of PRMT7. We confirmed that PRMT7 directly interacts with ASS1 using pull-down studies. ASS1 catalyzes the rate-limiting step of arginine synthesis in urea cycle and citrulline-nitric oxide cycle. We mapped the interface of PRMT7–ASS1 complex through computational approaches and validated the predicted interface in vivo by site-directed mutagenesis. Evolutionary analysis revealed that the ASS1 residues important for PRMT7–ASS1 interaction have co-evolved with PRMT7. We showed that ASS1 mutations linked to type I citrullinemia disrupt the ASS1–PRMT7 interaction, which might explain the molecular pathogenesis of the disease. Graphical Abstract: Highlights: PRMT7 interacts with ASS1. PRMT7 binds between the C-terminal helix and the synthetase domain of ASS1. Citrullinemia mutations of ASS1 disrupt the interaction. The residues of ASS1, which are important for interaction, co-evolved with PRMT7.